Education for Sustainability in Poland – A Narrative Literature Review - Scrobota, Magda (Journal of Education Culture and Society, 2020)
As a member state of the European Union, Poland is committed to sustainability by endorsing the principles of sustainable development in its Constitution and adopting European standards. However, to overcome the societal, environmental and economic demands, a society needs to integrate sustainability concepts into daily practices, education playing a crucial role in achieving this objective. This paper aims to provide an overview of the education for sustainability in Poland and its impact on Polish society. Designed as a narrative literature review, the paper reports on how education for sustainability was carried out between 1994 and 2013, building a detailed picture of the educational programs and actions conducted in business and non –profit organizations. Additionally it is revealed that although challenging, creating community-based learning can increase people’s awareness and potential to contribute to a sustainable future by reducing the de-coupling effect between organizational actual practices and declarations.